Effect of the inclusion of soybean oil in the diet of dairy goats on meat fatty acid composition of their suckling kids - Mele M.; Serra A.; La Comba F.; Buccioni A.; Conte G.; Secchiari P. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Ten lactating Saanen goats and their suckling kids were randomly assigned to two isonitrogenous diets: control diet (C) or soybean oil diet (SO); the two diets differed only by the inclusion of soybean oil (100 g/d in SO diet). At one month of age kids were slaughtered and from each one three muscle samples were collected: longissimus dorsi (LD), caput longum triceps brachii (CLOTB) and semimembranosus (SM). Lipids of milk and meat samples were extracted and analysed for fatty acid (FA) composition. Results showed that milk fat from goats fed the SO diet was richer in vaccenic acid and rumenic acid that increased respectively more than 500% and 600% if compared to C diet. With SO diet, also the other trans isomers of octadecenoic acid increased, included trans-10 C18:1, while saturated and medium chain fatty acid levels decreased. The intramuscular lipid content of kids fed SO milk resulted lower than that of kids fed C milk (1.58 g/100 g sample vs 1.81 g/100 g sample). The FA composition of intramuscular lipids of kids fed SO milk showed higher trans C18:1 and CLA isomers proportions (1.15 vs 0.2 and 0.81 vs 0.26 g/100 g extracted fat, respectively for vaccenic acid and rumenic acid), while lower levels of saturated FA, branched chain FA, oleic acid and n-3 unsaturated FA (UFA) as compared to that from kids fed C milk. The ratio between cis-9 monounsaturated FA and their tissue precursors in the ?9 desaturation pathway was negatively affected by the SO milk, especially for the rumenic acid/vaccenic acid pair. The n-6/n-3 ratio in the intramuscular lipids of kids fed C milk resulted lower than that of kids fed SO milk (5.25 vs 6.19, respectively).
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)